MAIN PROBLEMS OF MODERN MODIFYING OF ALLOYS. SOLUTIONS - V. Yu. Stetsenko (Литьë и металлургия, 2016)
It is shown that the main problems of modern modifying of alloys are connected with the air atmosphere and use of impurity modifiers. For the solution of these problems it is necessary to use the accelerated hardening, fine-crystalline furnace charge and protection against atmospheric vapors of water.